1996
DOI: 10.1016/0014-5793(96)00638-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐activity relationships in the peptide antibiotic nisin: antibacterial activity of fragments of nisin

Abstract: The post-translationally modified peptide antibiotic nisin has been cleaved by a number of proteases and the fragments produced purified, characterised chemically, and assayed for activity in inhibiting the growth of Lactococcus lactis MG1614 and Micrococcus luteus NCDO8166. These results provide information on the importance of different parts of the nisin molecule for its growth-inhibition activity. Removal of the C-terminal five residues leads to approximately a 10-fold decrease in potency, while removal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
160
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(172 citation statements)
references
References 21 publications
10
160
1
1
Order By: Relevance
“…The activity of nisin- (1-22) is about 10-fold higher than that reported for nisin-(1-20) [8,9]. Previously, Rink et al argued that the relatively high intrinsic antimicrobial activity of nisin-(1-22) might result from the positively charged Lys22 which counterbalances the negative charge of the C-terminal carboxyl group [8].…”
Section: Engineering Anionic and Cationic Tails In Nisin-(1-22)mentioning
confidence: 90%
See 1 more Smart Citation
“…The activity of nisin- (1-22) is about 10-fold higher than that reported for nisin-(1-20) [8,9]. Previously, Rink et al argued that the relatively high intrinsic antimicrobial activity of nisin-(1-22) might result from the positively charged Lys22 which counterbalances the negative charge of the C-terminal carboxyl group [8].…”
Section: Engineering Anionic and Cationic Tails In Nisin-(1-22)mentioning
confidence: 90%
“…Studies on the activity of truncated nisin mutants showed that nisin-(1-32)-NH 2 , nisin-(1-29) and nisin- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) have respectively slightly higher, about 10-fold lower and 100-fold lower activity than nisin [9]. Rink et al found that nisin-(1-22) has only 10-fold lower activity than nisin and suggested that the positively charged Lys22 might enhance binding to the negatively-charged bacterial membrane [8].…”
Section: Open Accessmentioning
confidence: 99%
“…One possible explanation is the modification of only one amino acid, which has already been shown to alter or prevent the activity of certain mutacins (Mulders et al, 1991;Rollema et al, 1995;Chan et al, 1996). The inhibition assay previously performed (Kamiya et al, 2005) could also result from the production of more than one inhibitory substance, showing that the understanding of the genetic determinants of several mutacins still needs to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…[34,35] In the present study, the lipid II binding affinities of mimics 1-7 were evaluated and compared with those of the native AB and ABC fragments 41 and 42, respectively. The native AB and ABC fragments were obtained by trypsin and chymotrypsin digestion of nisin A, respectively, according to Chan et al [36] In a typical experiment, preincubation of CF-loaded DOPClipid II vesicles with AB(C) fragments 1-7, 41, and 42 should result in the occupation of nisin-binding sites of lipid II. Depending on the affinity of the synthetic AB(C) fragments toward lipid II, subsequent addition of full-length nisin will result in a reduced amount of pore formation and reduced fluorescence.…”
Section: Biochemical Evaluationmentioning
confidence: 99%